Meniscus tears in the setting of anterior cruciate ligament injury - Koji Nukuto; Efstathios Konstantinou; Anja Maximiliane Wackerle; Jaren C. Lagreca; Camila Grandberg; Yunseo Linda Park; Brooke Collins; Volker Musahl (Journal of Joint Surgery and Research)
Purpose: Meniscus tears in the setting of anterior cruciate ligament (ACL) injury can affect post-operative outcomes and stability when not treated correctly. To reduce post-operative osteoarthritis and to improve outcomes, accurate diagnosis and treatment options must be selected. The purpose of this review was to review recent evidence regarding biomechanics and diagnosis of meniscus injury as well as treatment options for meniscus tears, which are often complicated by ACL injuries. Methods: Studies and topics on concomitant meniscus tears in the presence of ACL injury were searched. Results: Various risk factors have been identified for meniscus tears associated with ACL injuries. As some meniscus tears are difficult to identify on magnetic resonance imaging (MRI), arthroscopic diagnosis of meniscal pathology plays a crucial role. Indications for meniscectomy should be limited due to subsequent exacerbation of post-operative instability and contribution to osteoarthritic changes. Although meniscal repair is the standard treatment for bucket handle tears, ramp lesions, lateral meniscus posterior root tears, and lateral meniscus oblique radial tears, non-operative treatment may be also effective to a certain extent for stable meniscal tears. However, the indication for non-operative treatment should be carefully considered owing to potential enlargement of the torn area. Conclusions: Inadequate treatment of concomitant meniscus tears can result in residual instability and poor outcomes despite successful ACL reconstruction. High-quality evidence on the long-term outcomes of meniscus tears complicating ACL injuries is scarce and hence future studies are required.